TATHWIR ADAWAT IKHTIBAR MAHARAH AL-QIRAAH BI ISTI'MAL KAHOOT FI AL-MADRASAH AL-TSANAWIYAH AL-HUKUMIYAH BI SUMATRA AL-GHARBIYAH - Rahmawati, Rahmawati; Mahesa, Jaka Imam (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2019)
This research aimed to make or produce reading skills test tool using Kahoot platform. This was a